Evidence for a critical role of ceruloplasmin oxidase activity in iron metabolism of Wilson disease gene knockout mice - Merle, Uta; Tuma-Kellner, Sabine; Herrmann, Thomas; Muntean, Valer; Volkmann, Martin; Gehrke, Sven; Stremmel, Wolfgang (Journal of gastroenterology and hepatology, 2010)
Background and Aim: Wilson disease is a genetic disorder associated with copper overload due to mutations within the ATP7B gene. Although copper and iron metabolism are closely linked, the influence of mutations of the ATP7B gene on iron homeostasis is unknown. Therefore, the present study was carried out to elucidate iron metabolism in Atp7b(−/−) mice, an animal model of Wilson disease. Methods: Hepatic iron content, serum iron parameters and blood hemoglobin levels of Atp7b(−/−) mice and wild type mice were studied. Hepatic and duodenal expression of iron metabolism-related genes was measured quantitatively by real-time reverse transcription-polymerase chain reaction and post-translational expression of Dmt1 was analyzed by immunoblot. Results: Atp7b(−/−) mice displayed copper accumulation (P < 0.001), slightly elevated hepatic iron content (P = NS), and a low serum ceruloplasmin oxidase activity (1.5 ± 1.9 U/L vs 18.9 ± 4.0 U/L, P < 0.001) when compared with wild type mice. Serum iron, serum transferrin saturation, and blood hemoglobin levels were significantly lower in Atp7b(−/−) mice compared with controls (121.2 ± 35.3 µg/dL vs 201.8 ± 34.9 µg/dL (P < 0.001); 44.0 ± 12.7% vs 68.0 ± 8.2% (P < 0.001); and 12.7 ± 0.2 g/dl vs 15.3 ± 0.1 g/dl (P < 0.001), respectively). Hepatic mRNA expression of hepcidin, TfR-1, TfR-2, hemojuvelin, and Dmt1 + IRE did not differ significantly between Atp7b(−/−) and wild type mice. In the duodenum of Atp7b(−/−) mice Dmt1 + IRE and hephaestin did not show any differences in their mRNA levels compared with wild type mice, while Dcytb mRNA expression was 1.7-fold increased compared with wild type mice (P = 0.01). Conclusion: Atp7b(−/−) mice demonstrated decreased serum iron parameters and hemoglobin levels most likely related to a low serum ceruloplasmin oxidase activity and not due to total body iron deficiency.